Asxl1 deficiency in embryonic fibroblasts leads to cellular senescence via impairment of the AKT-E2F pathway and Ezh2 inactivation - Hye Sook Youn (Nature Portfolio, 2017)
Abstract Although ASXL1 mutations are frequently found in human diseases, including myeloid leukemia, the cell proliferation–associated function of ASXL1 is largely unknown. Here, we explored the molecular mechanism underlying the growth defect found in Asxl1-deficient mouse embryonic fibroblasts (MEFs). We found that Asxl1, through amino acids 371 to 655, interacts with the kinase domain of AKT1. In Asxl1-null MEFs, IGF-1 was unable to induce AKT1 phosphorylation and activation; p27Kip1, which forms a ternary complex with ASXL1 and AKT1, therefore remained unphosphorylated. Hypophosphorylated p27Kip1 is able to enter the nucleus, where it prevents the phosphorylation of Rb; this ultimately leads to the down-regulation of E2F target genes as confirmed by microarray analysis. We also found that senescence-associated (SA) genes were upregulated and that SA β-gal staining was increased in Asxl1 −/− MEFs. Further, the treatment of an AKT inhibitor not only stimulated nuclear accumulation of p27Kip1 leading to E2F inactivation, but also promoted senescence. Finally, Asxl1 disruption augmented the expression of p16Ink4a as result of the defect in Asxl1-Ezh2 cooperation. Overall, our study provides the first evidence that Asxl1 both activates the AKT-E2F pathway and cooperates with Ezh2 through direct interactions at early embryonic stages, reflecting that Asxl1 disruption causes cellular senescence.